"A COMPARATIVE ANALYSIS OF THE NEW CIVIL SERVICE LAW IN ALBANIA IN VIEW OF THE COMMITMENTS UNDER OF THE STABILISATIONASSOCIATION AGREEMENT WITH THE EUROPEAN UNION". Issue 2 (2015) - Alimehmeti, Evis; Petrela, Iris
No abstract available